POTENSI KARBON PADA TEGAKAN HUTAN MANGROVE DI DESA SEBATUAN KABUPATEN SAMBAS - Mulyadi, .; Astiani, Dwi; Manurung, Togar Fernando (JURNAL HUTAN LESTARI, 2017)
This study aimed to obtain information on the amount of carbon stockin Sustainable Mangrove Park in Sebatuan village of Sambas district. The analysis of biomass, carbon stock, and canopy cover in mangrove forest applied survey method using a line with the continous plot. The placement of the lines started about 20 meters from the shore line until it reached the river on the other side, with 50 meters distance between lines. Within each line, a 10 x 10 meters plot were made for the assessment of tree and of tree canopy cover. The results showed dense canopy cover classes with the number of plots as many as 41 plots with 86,0 % canopy cover had stock of carbon of 31,04 tons/ha equivalent to 113,92 tons CO2/ha. Canopy cover class with the number of plots as many as 31 pieces with 57,4% canopy cover has a carbon stock of 22,22 tonnes/ha equivalent to 81,55 tons CO2/ha. Thess results suggested that canopy density affectthe amount of carbon stock, yet, the canopy cover class has a different potency.Keywords: Biomass, Carbon, Mangrove Forests